2013
DOI: 10.1111/cla.12066
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of clade support across the major lineages of moss phylogeny

Abstract: Relationships among the major branches of moss phylogeny are understudied compared with other major land-plant groups. We addressed this by surveying 14-17 plastid genes from taxa representing the major lineages, using different phylogenetic methods (parsimony, likelihood) and codon-and gene-based data partitioning schemes (likelihood). Our phylogenetic inferences generally corroborated the best supported clades across multiple recent studies, with comparable or higher levels of clade support here. We resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 57 publications
10
16
0
Order By: Relevance
“…In summary, our experiments with outgroup sampling regimes confirm the results of previous morphological (Smith, 1971;Smith Merrill, 2007) and molecular phylogenetic studies (Bell and Hyvönen, 2008;Chang and Graham, 2014), which indicate that polytrichaceous mosses represent a morphologically unique group with no known close living relatives (long branch). Our experiments also suggest that there is no way to root phylogenetic analyses of the Polytrichaceae that does not distort ingroup relationships.…”
Section: Do We Know How To Root the Polytrichaceae?supporting
confidence: 89%
See 2 more Smart Citations
“…In summary, our experiments with outgroup sampling regimes confirm the results of previous morphological (Smith, 1971;Smith Merrill, 2007) and molecular phylogenetic studies (Bell and Hyvönen, 2008;Chang and Graham, 2014), which indicate that polytrichaceous mosses represent a morphologically unique group with no known close living relatives (long branch). Our experiments also suggest that there is no way to root phylogenetic analyses of the Polytrichaceae that does not distort ingroup relationships.…”
Section: Do We Know How To Root the Polytrichaceae?supporting
confidence: 89%
“…3). Whereas this placement of Oedipodium is congruent with the results of recent molecular phylogenetic studies (Chang and Graham, 2014), Tetraphis is not recovered as sister to Oedipodium in these studies. The ingroup root is between a clade consisting of Psilopilum and Notoligotrichum and the rest of Polytrichaceae (Figs.…”
Section: Do We Know How To Root the Polytrichaceae?supporting
confidence: 84%
See 1 more Smart Citation
“…(, , ) demonstrated that data from even highly reduced and rapidly evolving plastid genes or plastomes can be used to place heterotrophic plants with confidence. We were particularly interested in characterizing the Buxbaumia plastome in light of its purported heterotrophic status, given the placement of this small genus as sister to all other members of Bryopsida, which is by far the most species‐rich class of mosses (e.g., Qiu et al., , ; Chang and Graham, , ; Liu et al., , ; Gitzendanner et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In the mosses, molecular analyses have also resolved many of the deep relationships, but there are still several critical nodes that remain contentious (e.g., Newton et al., ; Cox et al., ; Qiu et al., ; Chang and Graham, , ; Liu et al., ). Of these, the relationships among Takakiopsida, Sphagnopsida, and the rest of the mosses (i.e., whether Takakiopsida is sister to all other mosses or forms a clade with Sphagnopsida) are perhaps the most intriguing, as conflicting topologies are often recovered with strong support (Qiu et al., ; Chang and Graham, , ; Liu et al., , ; One Thousand Plant Transcriptomes Initiative, ). The source of this conflict is uncertain, but Chang and Graham () observed that relationships were sensitive to different model or method assumptions.…”
Section: Introductionmentioning
confidence: 99%